Establishment and validation of a ferroptosis-related prognostic signature for hepatocellular carcinoma - He, Yixian; Wu, Yunyang; Song, Mengqi; Yang, Yanlong; Yu, Yizhi; Xu, Sheng (Frontiers in Oncology, 2023)
Ferroptosis is recently recognized as a kind of iron-dependent cell death, which is associated with the progression of hepatocellular carcinoma(HCC). Because the prognosis of HCC is quite poor and the prognostic prediction has challenges, we conducted a study to analyze the influence of drivers of ferroptosis(DOFs) on the prognosis of HCC. In this study, the FerrDb database and the Cancer Genome Atlas(TCGA) database were applied to retrieve DOFs and information of HCC patients respectively. Univariate Cox regression, LASSO, and multivariate Cox regression analyses were carried out to identify the optimal prognosis model and calculate the risk score. Five DOFs were identified to develop as a prognostic signature. Then, univariate and multivariate Cox regression analyses confirmed that the risk score was able to be an independent factor for the prognosis of HCC. Subsequently, patients in the training cohort were divided into high- and low-risk groups based on the median risk score. Low-risk patients showed better overall survival(OS) than high-risk patients. Furthermore, it also had high internal consistency. Receiver operating characteristic(ROC) curve analysis confirmed the signature’s predictive capacity. Additionally, gene functional analysis and immune-related analysis were conducted to explore the underlying mechanism. There was a higher proportion of nTreg cell, Th1 cell, macrophage, exhausted cell and CD8+T cell in the high-risk group. The Tumor Immune Dysfunction and Exclusion(TIDE) scores suggested that high-risk patients could respond better to immunotherapy. Besides, the experimental results showed that some genes were differentially expressed between tumor and normal tissues. In summary, this five ferroptosis gene signature showed potential in predicting prognosis in patients with HCC and could also be regarded as a value biomarker for immunotherapy response in these patients.